The chain of legal violence against trans women: from the lack of protection against physical violence caused by the gendered Law to the resistance as a knowledge-producing subject - Bravo Valderrama, María Patricia (2019)
From the exposition of a sentence that has left unpunished the strangulation of a trans woman in the city of Iquitos, this article exposes, compiling empirical investigations, the situation of trans women in Peru. Through the presentation of human rights reports prepared by LGTBIQ collectives from 2004 to the present, the purpose of this analysis is to have references and inputs that allow us to outline what gender law can do to avoid impunity and to guarantee effective protection against the violence perpetrated, with particular cruelty, against these women.